1976
DOI: 10.1007/bf00422088
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic polypeptide ? A postulated new hormone: Identification of its cellular storage site by light and electron microscopic immunocytochemistry

Abstract: A peptide, referred to as pancreatic polypeptide (PP), has recently been isolated from the pancreas of chicken and of several mammals. PP is thought to be a pancreatic hormone. By the use of specific antisera we have demonstrated PP immunoreactivity in the pancreas of a number of mammals. The immunoreactivity was localized to a population of endocrine cells, distinct from the A, B and D cells. In most species the PP cells occurred in islets as well as in exocrine parenchyma; they often predominated in the panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
80
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(92 citation statements)
references
References 22 publications
12
80
0
Order By: Relevance
“…Furthermore, the relative abundance of different cell types may also vary depending on the location of the islet within the pancreas, as demonstrated for alpha-and PP-cells. Islets from the proximal (head) part of the rat pancreas contain relatively few alpha cells, but numerous PP-cells, whereas the relationship is reversed in the distal (tail) part [14,15]. Different isolation methods result in variable yields of islets and the origin of the islets will have a great influence on studies of e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relative abundance of different cell types may also vary depending on the location of the islet within the pancreas, as demonstrated for alpha-and PP-cells. Islets from the proximal (head) part of the rat pancreas contain relatively few alpha cells, but numerous PP-cells, whereas the relationship is reversed in the distal (tail) part [14,15]. Different isolation methods result in variable yields of islets and the origin of the islets will have a great influence on studies of e.g.…”
Section: Discussionmentioning
confidence: 99%
“…"Pancreatic polypeptide" is a 36-aminoacid peptide which has been isolated from the avian pancreas [9,10] and from the pancreas of several mammals, including man [11,12,13,14]. Cells containing "pancreatic polypeptide" have been demonstrated in the pancreas of chicken [21] and of a variety of other species [22,23,24]. Their ultrastrucrural characteristics have not been clearly defined, but Larsson et al [23] suggested that they correspond to the type V-cells of Deconinck et al [25].…”
Section: Discussionmentioning
confidence: 99%
“…Cells containing "pancreatic polypeptide" have been demonstrated in the pancreas of chicken [21] and of a variety of other species [22,23,24]. Their ultrastrucrural characteristics have not been clearly defined, but Larsson et al [23] suggested that they correspond to the type V-cells of Deconinck et al [25].…”
Section: Discussionmentioning
confidence: 99%
“…Glucagon, PP and somatostatin have also been demonstrated in cells of extra-pancreatic tissue such as those of the gastrointestinal tract (Hokfelt et al 1975;Larsson et al 1976;Leduque et al 1982) and more recently insulin-like material has been reported to be present in the brain (Baskin et al 1983;Birch et al 1984). A number of biologically active peptides previously found in the hypothalamus and other regions of the brain have now been shown to exist in the pancreatic islet.…”
Section: Introductionmentioning
confidence: 96%